DETERMINATION OF THE STABILITY OF FREIGHT CARS TAKING INTO ACCOUNT THE RAILWAY TRACK PARAMETERS - Shvets, A. O. (Science and Transport Progress, 2020)
Purpose. For prospective speed increase in the work is aimed to consider the complex conditions of the dynamic interaction of the railway track with rolling stock. The nature and level of this interaction depends both on the design of the unit of rolling stock, its state and speed, and on the design and condition of the track itself. Methodology. Evaluation of the possible rolling stock impact on the track was investigated by the analytical method. The track stress state was determined by calculation using dependencies between force factors and the characteristics of the stress-strain state of the track. When determining the static pressure of the wheel on the rail, the influence of rolling stock skews in the rail track according to the “herringbone” scheme is considered, in which the additional lateral effect of the wheel pairs of the bogies on the track structure is maximal. Findings. When conducting theoretical studies, the dependencies of the lift resistance coefficient by longitudinal forces were obtained taking into account various types of inertia forces on irregularities both on the wheel and on the rail thread. The values of the friction coefficient in the wheel-rail contact on the movement speed were also obtained. Originality. For the first time, the rules for calculating the railway track for strength and determining the dynamic loading of the rail carriage are combined. This improvement will make it possible to calculate the structural speed of the car based on the axial loads, inertia forces due to the wheel and rails` irregularities, and also take into account the longitudinal quasistatic forces arising in the train during braking modes. Practical value. Determination of the car lift resistance coefficient using the above methodology will allow a more thorough consideration and justification of the cause of wheelset derailment. The application of this calculation method will allow us to determine the strength of the railway track and the ballast layer, taking into account the uneven load of rail threads in the case of distortions of the freight rolling stock under the action of compressive quasistatic longitudinal forces.